A Case of Enzootic Nasal Adenocarcinoma in a Ewe. (30th September 2012) - Stowe, Devorah Marks; Anderson, Kevin L.; Guy, James S.; Linder, Keith E.; Grindem, Carol B.
Abstract : An approximately 2-year-old open Suffolk ewe presented to the North Carolina State University College of Veterinary Medicine Veterinary Health Complex for evaluation of a left nasal mass. An ultrasound-guided aspirate and core biopsies were performed. An epithelial neoplasia with mild mixed inflammation (neutrophils and plasma cells) was diagnosed on cytology and confirmed on histopathology. Immunohistochemistry (IHC), reverse transcriptase polymerase chain reaction (RT-PCR), and transmission electron microscopy were also performed. IHC and RT-PCR identified the presence of enzootic nasal tumor virus and confirmed the final diagnosis of enzootic nasal adenocarcinoma.